Analysis of the Implementation of Formative Assessment on Students' Conceptual Understanding in Chemistry Learning - Nisrina, Putri; Primawati, Rizka Indah; Nahadi, Nahadi (Hydrogen: Jurnal Kependidikan Kimia, 2025)
Formative assessment strategies in chemistry classrooms are essential for enhancing learning, identifying misconceptions, increasing student engagement, promoting metacognition, and supporting differentiation in the classroom. This study employs a systematic literature review (SLR) method to examine formative assessment strategies in high school chemistry classes. The review process follows the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Eleven articles were assessed using the Mixed Methods Appraisal Tool (MMAT), focusing on empirical studies published between 2019 and 2023. The article selection process utilized two databases: Scopus and Google Scholar. The key findings identified four main themes related to formative assessment in chemistry classrooms: implementation effectiveness, relationships, technology, and challenges. Further research recommendations include exploring various formative assessment methods and integrating innovative assessment tools with technology to enhance self-assessment and improve student outcomes.